Eighteenth-century art worlds : global and local geographies of art - Sloboda, Stacey; Yonan, Michael Elia (Bloomsbury Visual Arts, Bloomsbury Publishing Inc, 2019)
"While the connected, international character of today's art world is well known, the eighteenth century too had a global art world. Eighteenth-Century Art Worlds is the first book to attempt a map of the global art world of the eighteenth century. Twenty-one essays from a distinguished group of scholars explore both cross-cultural connections and local specificities of art production and consumption in Africa, the Americas, Asia, and Europe. The result is an account of a series of interconnected and asymmetrical art worlds that were well developed in the eighteenth century. Capturing the full material diversity of eighteenth-century art, this book considers painting and sculpture alongside far more numerous prints and decorative objects. Analyzing the role of place in the history of eighteenth-century art, it bridges the disciplines of art history and cultural geography, and draws attention away from any one place as a privileged art-historical site, while highlighting places such as Manila, Beijing, Mexico City, and London as significant points on globalized map of the eighteenth-century art world. Eighteenth-Century Art Worlds combines a broad global perspective on the history of art with careful attention to how global artistic concerns intersect with local ones, offering a framework for future studies in global art history."--Bloomsbury Publishing.